2017
DOI: 10.14233/ajchem.2017.20528
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of Automotive Polymeric Materials in Exposed to Pongamia pinnata Biodiesel

Abstract: Material compatibility with biodiesels and their blends should be verified on a case-by-case basis to ensure long term durability of storage tanks and pipelines. This paper aimed to investigate the degradation of physical properties such as mass, volume, tensile strength, hardness and change in surface morphology for polymers namely polypthalamide (PPA) and polyarylamide (PAA) upon exposure to Pongamia pinnata biodiesel (PPB) and blends. Static immersion tests in B0, B10, B20 and B100 were carried out at 25, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The overall compatibility sequence of polymers was found to be PAA > PPA for static and PPA > PAA for flow conditions. 14 Comparative studies of PTFE and NBR with B20D75E5, B0 (diesel 100%) and B100 (biodiesel 100%) blends showed that mass loss of NBR was higher than PTFE. Change in mass and volume of NBR is mainly attributed to the relaxation of polymer chain and absorption of solvent.…”
Section: Propertymentioning
confidence: 98%
“…The overall compatibility sequence of polymers was found to be PAA > PPA for static and PPA > PAA for flow conditions. 14 Comparative studies of PTFE and NBR with B20D75E5, B0 (diesel 100%) and B100 (biodiesel 100%) blends showed that mass loss of NBR was higher than PTFE. Change in mass and volume of NBR is mainly attributed to the relaxation of polymer chain and absorption of solvent.…”
Section: Propertymentioning
confidence: 98%
“…At 25, 50, and 70 °C, the compatibility of B0, B10, B20, and BD100 palm biodiesel blends with automotive polymeric materials such as polypthalamide and polyarylamide was examined. At higher temperatures, both polymeric materials showed a large mass increase . The impact of biodiesel’s molecular structure and feedstock on its compatibility with NBR was explored.…”
Section: Introductionmentioning
confidence: 99%
“…At higher temperatures, both polymeric materials showed a large mass increase. 24 The impact of biodiesel's molecular structure and feedstock on its compatibility with NBR was explored. It has been found that the fatty acid ester's carbon chain length, amount of double bonds, and alcohol moiety chain length all have a significant impact on its compatibility with the NBR.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The exposure of hoses to different fuels with the increasing blend ratio of biodiesel led to the degradation of tensile strength. Meenakshi investigated the compatibility of B0, B10, B20, and BD100 palm biodiesel blends with automotive polymeric materials including polypthalamide and polyarylamide at 25, 50, and 70 °C. Both polymeric materials revealed a significant mass increase at higher temperature.…”
Section: Introductionmentioning
confidence: 99%